PENERAPAN MODEL TGT (TEAMS GAME TOURNAMENT) BERBANTUAN ZEP QUIZ UNTUK MENINGKATKAN LITERASI SAINS SISWA PADA PEMBELAJARAN IPA - Zewelya Ray Prameswara Kuswantoro , Titania; Bintang Ilhami, Fasih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The results of the 2023 PISA survey indicate that students’ scientific literacy in Indonesia remains below the OECD average and tends to stagnate, thus requiring innovation in science learning. This study aims to determine the effect of the implementation of the Teams Games Tournament (TGT) learning model assisted by Zep Quiz in improving scientific literacy on the topic of the human digestive system. This research employed a quantitative descriptive approach with a pre-experimental method using a One Group Pretest-Posttest design. The research subjects were students who were given a pretest, followed by treatment using the TGT model assisted by Zep Quiz, and a posttest. Data collection techniques included observation, tests, and questionnaires. The results showed that students’ scientific literacy skills improved from an average of 58% in the pretest to 75% in the posttest. The paired sample t-test results showed a significance value of < 0.001 (< 0.05), indicating a significant effect of the application of the TGT model assisted by Zep Quiz on improving students’ scientific literacy. The N-Gain analysis showed varying improvements across indicators, with a low category in the indicator of designing and evaluating scientific investigations. Thus, the application of the TGT model assisted by Zep Quiz is effective in improving students’ scientific literacy.